Medicine, Sport and the Body A Historical Perspective - Carter, Neil (Bloomsbury Academic, 2012)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. What role does sports medicine play in today's society? Is it solely about treating sports injuries? Should it only be concerned with elite sport? This book provides a history of the relationship between sport, medicine and health from the mid-19th century to today. It combines the sub-disciplines of the history of medicine and the history of sport to give a balanced analysis of the role of medicine in sport and how this has evolved over the past two centuries. In an age where sports medicine plays an increasingly prominent role in both elite and recreational sport, this book provides a timely and clear analysis of its rise and purpose.